An Introduction to South Asian Politics - Edited by DeVotta, Neil (London Routledge, 2016)
This introductory textbook provides students with a fundamental understanding of the social, political, and economic institutions of six South Asian countries: Afghanistan, Bangladesh, India, Nepal, Pakistan, and Sri Lanka. It adopts a broad theoretical framework and evaluates the opportunities and constraints facing South Asia's states within the context of democracy. Key features include: - An introduction to the region. - The history and political development of these South Asian states, including evaluations of their democratic trajectories. - The management of conflict, economic development, and extremist threats. - A comparative analysis of the states. - Projections concerning democracy taking into consideration the opportunities and constraints facing these countries. This textbook will be an indispensable teaching tool for courses on South Asia. It includes pedagogical features such as political chronologies, political party descriptions, textboxes, a glossary and suggestions for further reading. Written in an accessible style and by experts on South Asian politics, it offers students of South Asian politics a valuable introduction to an exceedingly diverse region.
Include Boxes, Tables, Glossary and Index.
Neil DeVotta is an Associate Professor of Political Science at Wake Forest University. His research interests include South Asian security and politics, ethnicity and nationalism, and democratic transition and consolidation. He is the author of Blowback: Linguistic Nationalism, Institutional Decay, and Ethnic Conflict in Sri Lanka (2004) and the editor of Understanding Contemporary India, 2nd edition (2010).
Keywords: South Asia -- Politics and government -- Political science